Clarity first : how smart leaders and organizations achieve outstanding performance - Martin, Karen (McGraw Hill Education, 2018)
Award-winning business performance improvement and Lean management expert Karen Martin diagnoses a ubiquitous business management and leadership problem--the lack of clarity--and outlines specific actions to dramatically improve organizational performance. --